A Model of Multiple Magnetic Separation in the Continuous Process. (1999) - Brożek, M.
Abstract : In continuous enrichment processes, in industrial conditions and due to the generally required high efficiency of machines, a relatively high concentration of feed is applied. Since it is necessary to liberate the useful minerals, the feed has to be ground thoroughly and this fact results in the percentage growth of the fraction of particles measuring a few tens or several micrometers. When the particles are so fine and the feed is so much concentrated, the magnetic particles interactions play a significant role and they lead to the phenomenon of magnetic flocculation. The flocs contain the particles of waste rock and intergrowths. In order to obtain the final product of high quality the material is subjected to multiple enrichment operations. This paper presents a mathematical model of multiple magnetic separation in which the grade of the magnetic concentrate was expressed as the function of multiplication ratio of separation and the value of external forces acting on a particle as well as interactions of the magnetic particles. The dependence of the content of magnetic component in the highgradient separation concentrates on the multiplication ratio of separation, flow velocity of the suspension through the separator working space, the intensity of matrix vibration and the concentration of solid particles in the feed for the separation of magnetite ore was verified. The verification was carried out according to the author's own research and the reference.